2016
DOI: 10.1039/c5sc04796j
|View full text |Cite|
|
Sign up to set email alerts
|

Fatty acids' double role in the prebiotic formation of a hydrophobic dipeptide

Abstract: Fatty acids, hypothetical components of protocell membranes, are proved to enhance the prebiotic formation of a hydrophobic peptide when organized in supramolecular assemblies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 46 publications
3
41
0
3
Order By: Relevance
“…It also strengthens additional advantagesi nt erms of functiont hat can be obtained by associating amino acids with membranes or nucleic acids that have already been observed in our group as well as by others. [9][10][11][12] Diversity in prebiotic "clutter" [56] can also present advantages in terms of as elf-organization process. The emergence of translation may therefore lie in the intimate chemistry of RNA and the specific behavior of the intramolecular transfer in 3'phosphorylated RNA as well as in the very specific behavior of the ribose 2'-and 3'-hydroxyl groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It also strengthens additional advantagesi nt erms of functiont hat can be obtained by associating amino acids with membranes or nucleic acids that have already been observed in our group as well as by others. [9][10][11][12] Diversity in prebiotic "clutter" [56] can also present advantages in terms of as elf-organization process. The emergence of translation may therefore lie in the intimate chemistry of RNA and the specific behavior of the intramolecular transfer in 3'phosphorylated RNA as well as in the very specific behavior of the ribose 2'-and 3'-hydroxyl groups.…”
Section: Resultsmentioning
confidence: 99%
“…The question of the origin of life is now considered as that of co-evolution of different subsystems rather than as elf-organization process in as ystem made of as ingle biopolymer.I th as therefore been considered as ac o-evolutionary process [1][2][3] that overcomes the difficulties associated with past views on the origin of lifes tartingf rom as ingle kind of biopolymer.P revious review articles have demonstrated the advantages that could be expected from system chemistry views [4,5] associating differents ubsystems with each other. [6,7] Experimental approaches have indeed shown the benefits resulting from the association of components coming from different subsystems for self-organization, as in the cases of the combination of peptides andn ucleotides, [8] peptides and lipids, [9] or nucleic bases and fatty acids. [10] As trong support to these views has recently been brought about by the discovery that most of the essential building blockso fb iochemistry can be formed from very similar processes possibly occurring in the same location.…”
Section: Introductionmentioning
confidence: 99%
“…18 As argued in Ruiz-Mirazo and Moreno (2013). Examples of this use of definitions are Guiloff (1981), Fleischaker (1990), Luisi (1993), Murillo-Sanchez et al (2016). Stano and Mavelli (2015).…”
Section: General Roles and Applications In Different Fields At The Frmentioning
confidence: 99%
“…10 Fmoc (9-fluorenylmethyloxycarbonyl) group contributes to enhance the self-assembly of the dipeptides onto well-defined nanostructures through solvophobic interactions, also providing amphiphilic character. [11][12][13] Selfassembly of Fmoc-dipeptides in bulk solution is able to render nanowires with excellent chirality and energy transfer features. 14,15 Intriguingly, self-assembled nanowires of dipeptides are connected to the core recognition motif in Alzheimer disease.…”
Section: Introductionmentioning
confidence: 99%